DETERMINAN PERATAAN LABA PADA PERUSAHAAN INDEKS LQ 45 DI BURSA EFEK INDONESIA PADA TAHUN 2016 – 2018 - Wachidah Fauziyanti; Esa Firda Eryliana (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2022)
Purpose of study this is analyze effect of return on assets, financial leverage, size company , net profit margin against alignment profit . The analytical method used are descriptive statistics and logistic regression with previously already model feasibility test and assumption test were carried out classic . Data collection was carried out with documentation sourced secondary data _ from report LQ45 index company finance listed on the Indonesia Stock Exchange for the 2016-2018 period . ROA research results have no negative effect significant , financial leverage has an effect positive , size company take effect positive and influential NPM positive significant to income smoothing . Advice for study for add sample and expand type company as well as enter a new variable that has effect to alignment profit